2014
DOI: 10.1155/2014/632376
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of GABAergic Transmission Modulation as a Novel Functional Target for Management of Multiple Sclerosis: Exploring Inhibitory Effect of GABA on Glutamate-Mediated Excitotoxicity

Abstract: Multiple sclerosis (MS) is an autoimmune inflammatory disease of the central nervous system (CNS) where the communication ability of nerve cells in the brain and spinal cord with each other gets impaired. Some current findings suggest the role of glutamate excitotoxicity in the development and progression of MS. An excess release of glutamate leads to the activation of ionotropic and metabotropic receptors, thus resulting in accumulation of toxic cytoplasmic Ca2+ and cell death. However, it has been observed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Furthermore, the fact that cognitive impairments are related to the levels of excitatory and inhibitory neurotransmitters in the hippocampus of patients in the remitting stage rather than in the progressive stage (Cawley et al, 2015) helps to address a problem regarding the window of opportunity for clinical intervention. A previous animal study also supports the potential of using positive GABA receptor modulators to manage MS (Gilani, Dash, Jivrajani, Thakur, & Nivsarkar, 2014). Therefore, pharmacological therapies targeting these neurotransmitter systems might be valuable in the future.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, the fact that cognitive impairments are related to the levels of excitatory and inhibitory neurotransmitters in the hippocampus of patients in the remitting stage rather than in the progressive stage (Cawley et al, 2015) helps to address a problem regarding the window of opportunity for clinical intervention. A previous animal study also supports the potential of using positive GABA receptor modulators to manage MS (Gilani, Dash, Jivrajani, Thakur, & Nivsarkar, 2014). Therefore, pharmacological therapies targeting these neurotransmitter systems might be valuable in the future.…”
Section: Discussionmentioning
confidence: 60%
“…Inflammation in EAE is related with calcium overload of neurons and manifested process of excitotoxicity in which the release of glutamate is a crucial manifestation. Such changes are the main events during the relapse phase of EAE, accordingly, increased GABA expression could indicate suppressed excitotoxicity and promoted inhibitory neuronal pathways [12]. Therapeutic procedures of both TBS induced important changes in investigated molecules expressions, such as BDNF elevation.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, alprazolam, another benzodiazepine derivative, also decreased the severity of clinical, histological and neuroendocrine manifestations of EAE in Lewis rats but only when the animals were exposed to stressful conditions [14]. In the context of EAE, it was also observed that phenobarbitone sodium and sodium valproate inhibited the clinical signs of EAE; however, high doses of diazepam failed to control EAE signs in this experiment [15]. …”
Section: Introductionmentioning
confidence: 93%